2009
DOI: 10.1002/jmri.21879
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of endometrial carcinoma for preoperative staging at 3.0 T: Comparison with imaging at 1.5 T

Abstract: Purpose:To prospectively compare magnetic resonance imaging (MRI) at 3.0 T and 1.5 T in the same patients for preoperative evaluation of endometrial carcinoma. Materials and Methods:Thirty consecutive patients with endometrial carcinoma underwent MRI at both 3.0 T and 1.5 T as well as surgery. Quantitative and qualitative analyses were performed. Two radiologists independently evaluated images. MR findings were compared with surgicopathologic findings.Results: Image homogeneity of T2-weighted images at 3.0 T w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 33 publications
1
28
2
Order By: Relevance
“…Three previous studies on interobserver variation in the preoperative MRI staging of endometrial carcinomas included only two observers [16][17][18]. Hori et al [16] reported good interobserver agreement on T2-weighted imaging for deep myometrial invasion (κ00.66/0.67 at 3.0 T and 1.5 T, respectively), cervical stroma invasion (κ00.77/0.76), and lymph node metastases (κ00.64/0.74).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Three previous studies on interobserver variation in the preoperative MRI staging of endometrial carcinomas included only two observers [16][17][18]. Hori et al [16] reported good interobserver agreement on T2-weighted imaging for deep myometrial invasion (κ00.66/0.67 at 3.0 T and 1.5 T, respectively), cervical stroma invasion (κ00.77/0.76), and lymph node metastases (κ00.64/0.74).…”
Section: Discussionmentioning
confidence: 96%
“…Among the numerous papers published in the last few decades on MRI in endometrial carcinomas [15], few reports presented data on interobserver agreement, and then only for two observers [16][17][18][19][20][21]. The aims of this study were to evaluate the degree of agreement between several radiologists on pelvic MRI findings of deep myometrial invasion, cervical stroma invasion and lymph node metastases in endometrial carcinomas, and to compare these imaging findings with results from surgical staging.…”
Section: Introductionmentioning
confidence: 96%
“…The imaging characteristics of myometrial invasion include disruption of the junctional zone observed by T2-weighted imaging (T2WI) or discontinuity on early subendometrial contrast enhancement by dynamic contrast-enhanced imaging (DCE) (2). The accuracy of detecting myometrial invasion by endometrial cancer using T2-weighted images varies between 77% and 87% (3)(4)(5), whereas that using DCE is about 89%-91% (4,(6)(7)(8)(9). Recent reports suggest that the diagnostic accuracy of a combination of diffusionweighted imaging (DWI), T2WI, and DCE is more than that of imaging without DWI (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…33 This could be important with the increased use of 3T MR systems over the past several years to image a variety of areas, including the fe- male pelvis. [34][35][36][37] However, acquisition time can be shorter with the dual-echo Dixon than the IDEAL technique, which requires 3 echoes, and thereby yield fewer motion artifacts. We think a comparison of pelvic imaging between the 2 techniques is needed.…”
Section: Discussionmentioning
confidence: 99%